Textos e contextos educativos que promovem aprendizagem - optimização de um modelo de prática pedagógica - Ana Maria Morais; Isabel Pestana Neves (Universidade do Minho, 2009)
Along twenty years of research we have looked for answers to the major problem of improving students learning, particularly of the disadvantaged, without decreasing the level of conceptual demand. The research has been focused on various contexts: contexts of school and family learning, contexts of teacher education and contexts of syllabuses and textbooks construction. In order to direct the research and to analyse the results we have constructed specific models. Successive approximations led to a model that conceptualises a pedagogic practice that seems to have the potential to lead children to success at school, narrowing the gap between children from differentiated social backgrounds. Bernstein's theory of pedagogic discourse has provided the main theoretical framework to our studies. This article intends to present the model and describe its characteristics, to show the model at work and to discuss its optimization. A new improved theoretical model, derived from that optimization, will be tested in future research.